2018
DOI: 10.1111/jfb.13807
|View full text |Cite
|
Sign up to set email alerts
|

Benthic habitat selection in juvenile European eel Anguilla anguilla: implications for coastal habitat management and restoration

Abstract: The critically endangered European eel Anguilla anguilla is dependent on suitable habitat qualities over a vast geographic area. Even though a significant proportion of the population never enters fresh water, the preferred benthic habitat is largely unknown in the marine environment. Examining substratum selection in A. anguilla reveals that elvers prefer coarse gravel, suggesting that conservation efforts may benefit from targeting this type of substratum in marine coastal areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Without contradicting these findings, the probability of eel occurrence in our study was significantly higher in specific riverine habitats than others. Moreover, our results are corroborated in an experimental study of elvers in marine habitat, where coarse substrate was preferred (Christoffersen et al 2018). In experimental studies on yellow eel, Nyman (1972) showed that eels were highly selective with regard to bottom substrate, with a shift from hibernating in soft bottom (mud) at low temperatures to hiding in coarse bottom substrate at water temperatures [ 8-9°C.…”
Section: Habitat Usesupporting
confidence: 80%
“…Without contradicting these findings, the probability of eel occurrence in our study was significantly higher in specific riverine habitats than others. Moreover, our results are corroborated in an experimental study of elvers in marine habitat, where coarse substrate was preferred (Christoffersen et al 2018). In experimental studies on yellow eel, Nyman (1972) showed that eels were highly selective with regard to bottom substrate, with a shift from hibernating in soft bottom (mud) at low temperatures to hiding in coarse bottom substrate at water temperatures [ 8-9°C.…”
Section: Habitat Usesupporting
confidence: 80%
“…These results agree with those of previous studies on microhabitat uses in other young anguillid eels (Johnson & Nack, ; Laffaille et al, ). In fact, these animals have been reported to settle and hide in various types of riverbed materials (Aoyama et al, ; Christoffersen et al, ; Tomie et al, ). This suggests that substrate complexity is an important factor determining microhabitat use of young eels.…”
Section: Discussionmentioning
confidence: 99%
“…Their growth rate in coastal/brackish waters is higher than that in freshwaters (Kaifu, Miller, Yada, et al, ; Yokouchi et al, ), as shown in other anguillids (Cairns, Secor, Morrison, & Hallett, ; Daverat & Tomás, ). Yellow eels are known to use various types of riverbed materials as refuges to avoid predators and fast flows (Aoyama, Shinoda, Sasai, Miller, & Tsukamoto, ; Christoffersen et al, ; Tomie et al, ). Even though there are several studies about across‐life‐stage distribution of eels in rivers, including for Japanese eels (e.g., White & Knights, ; Lasne & Laffaille, ; Yokouchi et al, ; Kwak, Engman, & Lilyestrom, ), the use of micro‐ and reach‐scale habitats by elvers and early yellow eels (hereafter referred to as “young eels”) in natural environments is not sufficiently studied (Johnson & Nack, ; Laffaille et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Elvers have been indicated to prefer coarse and heterogeneous habitats ( e.g ., Christoffersen et al ., 2018; Degerman et al ., 2019; Silberschneider et al ., 2004), whereas elver substrate choice in the absence versus presence of predator cues has to our understanding hitherto not been experimentally examined. If habitats differ in protection from predation, perceived predator presence could affect habitat choice.…”
Section: Figurementioning
confidence: 99%